Bio-pics : a life in pictures - Cheshire, Ellen (Short cuts (London, England), 2015)
Bio-pics: A Life in Pictures offers a series of case studies which throw light on this most unique of genres. Is the bio-pic a genre in its own right? Or are such films merely footnotes in other more traditional genres such as the western or costume drama, depending on the historical figure under scrutiny. Unlike other genre forms bio-pics seemingly share no familiar iconography, codes or conventions. They can be set anywhere and at any time. What links them is quite simply that the films depict the life of an 'important' person. Through a carefully selected range of thematically linked (English-language) bio-pics released since 1990 this book explores key issues surrounding their resurgence, narrative structure, production, subject representation or misrepresentation, and critical response. The films under discussion are grouped around a profession (writers, singers, politicians, sportsmen, criminals, artists) allowing for comparisons to be drawn in approaches to similar subject matter. -- Provided by publisher.